38 Improving bystander defibrillation in out-of-hospital cardiac arrests at home. (26th April 2019) - Karlsson, L; Malta Hansen, C; Vourakis, C; Sun, CLF; Rajan, S; Bach Søndergaard, K; Andelius, L; Lippert, F; Gislason, G; Chan, TCY; Torp-Pedersen, C; Folke, F
Abstract : Background: Most out-of-hospital cardiac arrests occur at home with dismal bystander defibrillation rates (1–3). We investigated the proportion of home arrests potentially reachable with an automated external defibrillator (AED) before emergency medical service (EMS) arrival according to different bystander activation strategies. Method: We identified cardiac arrests in homes (private/nursing/senior homes) and registered AEDs in Copenhagen, Denmark (2008–2016). AED coverage (distance from arrest to AED) and accessibility at the time of arrest were examined according to route distance to nearest AED and EMS response time. The proportion of arrests reachable with an AED was calculated for two-way (from patient to AED and back) and one-way (from AED to patient) bystander response scenarios. Results: Of 1879 home arrests, AED coverage ≤100 m was low (6.3%) and nearly halved due to AED inaccessibility. A two-way bystander could potentially retrieve an accessible AED (≤100 m) prior to EMS in 31.1% (n=37) of cases. If a bystander only needed to travel one-way to bring an AED (≤100 m, ≤250 m and ≤500 m), 45.4% (n=54/119), 37.1% (n=196/529) and 29.8% (n=350/1174) could potentially be reached before EMS based on current AED accessibility. Assuming 24/7 AED accessibility, the proportions increased to 76.5%, 68.6%, 47.8%, respectively. Conclusion: Few home arrests would be reachable with an AED before EMS if bystanders need to travel to fetch the AED and back to the patient. However, nearly 1/3 of arrests≤500 m of an AED could be reached by a bystander before EMS traveling one-way to the patient, increasing to nearly half of all home arrests if all AEDs were 24/7 accessible. References: Perkins GD, Handley AJ, Koster RW, Castren M, Smyth MA, Olasveengen T, et al . European Resuscitation Council Guidelines for Resuscitation 2015: Section 2. Adult basic life support and automated external defibrillation. Resuscitation 2015;95:81–99. Rea T. Paradigm shift: changing public access to all-access defibrillation. Heart 2018;104(16):1311–2. Sun CL, Demirtas D, Brooks SC, Morrison LJ, Chan TC. Overcoming Spatial and Temporal Barriers to Public Access Defibrillators Via Optimization. J Am Coll Cardiol 2016;68(8):836–45. Conflict of interest: Dr. CM Hansen, Dr. F Folke, and Dr. F Lippert received research grants from the Laerdal Foundation. None of the other authors reported anything to disclose. Funding: Dr. L Karlsson, Dr. CM Hansen, Dr. F Folke, and Dr. L Andelius received unrestricted funding from the private Foundation TrygFonden.